The Differences of Language Use between Males and Females in Sundanese Language in Informal Conversation - Rani Ligar Fitriani; Sinta Siti Sundari; Nijar Kurnia Romdoni (JALL (Journal of Applied Linguistics and Literacy), 2023)
ABSTRACTOral language has an important role in human life. Oral language is used in both formal and informal communications. In fact, in everyday life humans use oral language more than writing. Oral language can take the form of lectures, stories, discussions, teaching, sermons, oral reports, conversations, and speeches. The most common oral language activity is conversation. Conversations are influenced by various factors, including: gender, age, occupation, location, content, situation, and purpose. Men and women as part of society, are used to having conversations, both with family, teachers, neighbors and friends. In reality, the languages spoken by men and women are very different. This can be seen from the way they speak. This study aims to find out how the differences in the languages used by men and women in informal Sundanese conversations on campus and find out the factors that influence the appearance of differences in the languages used by men and women in informal Sundanese conversation on campus. This research is a qualitative research. In this study, researchers took a sample of 4 students from Siliwangi University, Faculty of Teacher Training and Education who were selected using a purposive sampling technique. Based on observations and interviews, the results obtained are that in general, the differences in the language used by men and women in informal Sundanese conversations on campus are that men use more harsh and impolite words when speaking, while women are more polite and more use soft words when speaking. While the factors that influence the emergence of differences in the languages used by men and women in informal Sundanese conversations on campus include association, environment, native culture, habits, family and friends.